PENERAPAN TANGGUNG JAWAB KOMANDO DALAM MILITER PADA PELANGGARAN HAM BERAT DI INDONESIA - Khair, Taufiqul Hidayat; Wahyuni, Sri (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2023)
This study examines how the implementation of command accountability in the military on gross human rights violations. This research is normative legal research is prescriptive. Types of legal materials include primary and secondary legal materials. Primary Legal Material: NRI Constitution 1945, Law No. 39 of 1999 on Human Rights, Law No. 26 of 2000 on Human Rights Courts, Association of Decisions pn, PT, MA in human rights cases. Secondary legal material: Textbooks written by legal experts, legal journals, research in the form of thesis and thesis, and scientific papers. The technique of collecting legal materials is obtained through literature studies through complaint report data, books, journals, and also directly through interviews. The results showed that the application of command responsibility in the military to gross human rights violations in Indonesia applies to crimes of genocide and crimes against humanity. The application of command accountability in the military to gross human rights violations in Indonesia is tried and decided based on the relationship between superiors and subordinates, between the perpetrator and the accused who has fulfilled the elements of involvement, relationship, and knowledge of the commander who has the authority to commit crimes committed by his subordinates. So if these elements are not met then one cannot be criminally prosecuted based on the doctrine of command responsibility.